Tolerance of Earthworms in Soil Contaminated with Polycyclic Aromatic Hydrocarbon - Rubiyatno; Teh, Zee Chuang; Lestari, Diah Velentina; Yulisa, Arma; Musa, Muthah; Chen, Tse-Wei; Darwish, Noura M.; AlMunqedhi, Bandar M.; Hadibarata, Tony (Industrial and Domestic Waste Management, 2022)
Pyrene is a very resistant polycyclic aromatic hydrocarbon (PAH) with four benzene rings that survives in the environment. This study was aimed at investigating the tolerance of earthworms in soil contaminated with pyrene. The studies were performed by employing earthworms gathered from shady regions adjacent to sewage ponds as pyrene degraders to eradicate pyrene from the soil. Numerous factors affecting pyrene degradation efficiency were explored, including the effect of contaminant concentration, earthworm and soil ration, and soil condition. The highest pyrene removal (31.2%) was shown by earthworms in the condition of soil mixed with cow dung. Pyrene decomposition was inhibited during soil sterilization due to the absence of soil microorganisms and indigenous pyrene-degrading bacteria. Nonetheless, earthworms are suitable for use as pyrene degraders in contaminated soil.